Process tracing change management: the reform of the Italian judiciary. Issue 5 (4th June 2018) - Busetti, Simone; Vecchi, Giancarlo
Abstract : Purpose: In 2009, the Italian Government initiated a national programme to improve the management of judicial offices. Programme implementation has been patchy and unsatisfactory in all but a few cases. Against this background, the Law Court of Milan has achieved exceptional results and is now recognised as a good practice benchmark for Italy. The purpose of this paper is to investigate this case in order to reconstruct the local conditions for successful implementation of the national programme. Design/methodology/approach: To test a theory of the programme based on leaders' engagement, their access to managerial knowledge, and the transfer and consolidation of that knowledge, the present study applies process tracing, a qualitative method that uses Bayesian reasoning to improve the accuracy of within-case inferences. Findings: The analysis shows how programme and context features interacted to support change. In particular, while the national programme succeeded in providing resources for leader engagement and knowledge access, the transfer and consolidation of managerial knowledge depended largely on a brokerage function performed locally between consultants and magistrates. Originality/value: The paper sheds light on the local conditions for change management and does so by employing an innovative qualitative method that improves the reliability of within-case inferences.